UJI DAYA HASIL BEBERAPA GENOTIPE SORGUM MANIS (Sorghum bicolor (L.) Moench) KOLEKSI BATAN - Tarigan, Joel Alvius; Zuhry, Elza; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of the research was to determine of yield potential 13 genotypes sweet sorghum and to get of 13 genotypes sweet sorghum to have high productivity. This research has conducted in field experiment and Plant Breeding Laboratory Faculty of Agriculture University of Riau, Pekanbaru, from April 2013 to September 2013. The data were analyzed by analysis of variance consist of 13 treatments and 3 replications that contained 39 experimental units. These treatments consist of BATAN’s sweet sorghum strains, there are Patir-1, Patir-2, Patir-3, Patir-4, Patir-5, Patir-6, Patir-7, Patir-8, Patir-9, Patir-10 and 3 sweet Sorghum varieties as a comparison, there are Kawali, Mandau and Pahat. The genotypes treatments were significantly affect to plant height, number of segments per plant, panicle length, main panicle of seed weight, weight of 1000 seed but not significant affect of stem diameter, days to flowering, and seed weight /m2. Genotypes tested the ability of growth and yield different each genotypes. Genotypes   Patir-10 has the highest of seed weight are 3.78 ton /ha compared to other genotypes. Keywords : Sorghum bicolor, growth, genotypes, yield potential.